ANALISIS RAB STRUKTUR BETON GEDUNG TAMAN BUDAYA MENGGUNAKAN REVIT - Prio Prio; Agung Dwi Putra; M. Afif Shulhan; Dimas Langga Candra Galuh (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2025)
Along with the development of technology and various technological advancements in the construction sector, the use of Building Information Modeling (BIM) technology has increased, as some budget planning methods still use conventional/analytical methods. This study was conducted to determine the accuracy of the BIM and analytical methods in preparing the Cost Budget Plan (RAB) by comparing the RABs of both methods. The results obtained from the comparison of concrete and reinforcement volume requirements using the analytical method were higher than those using the BIM (Building Information Modeling) method, with differences of 6,430 m3 (1.16%) and 2,293.102 kg (2.63%), respectively. The difference in concrete and reinforcement costs between the BIM (Building Information Modeling) method and the analytical method was higher, at Rp 8,065,990.45 and Rp 114,601,701.09, respectively, with a concrete cost ratio of 1.11% and reinforcement cost of 1.94%. The total Cost Budget Plan (RAB) using the analytical method was 0.71% higher by Rp 56,846,733.08 than the Building Information Modeling (BIM) method, with a total Cost Budget Plan (RAB) of only Rp 7,925,716,320.58 and a total Cost Budget Plan (RAB) using the analytical method of Rp 7,982,563,053.